IMPLEMENTASI PILAR PEMBANGUNAN HUKUM : EDUKASI PARENTING (POLA ASUH) SEBAGAI UPAYA PENANGGULANGAN KEKERASAN TERHADAP ANAK DI PPS PGOT MARDI UTOMO SEMARANG - Febriani, Niken Ayu (Sekolah Vokasi Universitas Diponegoro, 2024)
Panti Pelayanan Pengemis, Gelandangan, dan Orang Terlantar Mardi Utomo (PGOT Mardi Utomo), located in Kramas Village, Tembalang, is a social institution that provides social welfare by providing social rehabilitation facilities for beggars, homeless people and abandoned people. Many existing beneficiaries also often bring their problems, especially regarding child-rearing patterns. Vulnerable beneficiaries often do not have sufficient knowledge about parenting patterns so there is a need for provision and socialization regarding appropriate parenting patterns and minimizing violence, this paper aims to provide knowledge and explanation of appropriate parenting patterns and minimizing violence directed at people. old. On the other hand, the beneficiaries will also one day leave their underwear behind so they also need to be provided with material about child trafficking to create attention and awareness towards children. This writing uses observation, lecture, and question-and-answer discussion methods. As a result, parents already understand what appropriate parenting styles are and have implemented fairly appropriate parenting patterns. Besides that, parents also understand what human trafficking is and its indications.